ChemInform Abstract: Waol A (I), trans‐Dihydrowaol A (II), and cis‐Dihydrowaol A (III): Polyketide‐Derived γ‐Lactones from a Volutella Species. Issue 46 (24th October 2013) - El‐Elimat, Tamam; Figueroa, Mario; Raja, Huzefa A.; Adcock, Audrey F.; Kroll, David J.; Swanson, Steven M.; Wani, Mansukh C.; Pearce, Cedric J.; Oberlies, Nicholas H.
Abstract The γ‐lactones (I) and (II) are tested against two cancer cell lines, whereas compound (I) displays moderate cytotoxic activity against the SW‐620 cancer cell line, compound (II) shows no activity.